Marital Status as a Partial Mediator of the Associations Between Young Adult Substance Use and Subsequent Substance Use Disorder: Application of Causal Inference Methods - Jang, Bohyun Joy (J Stud Alcohol Drugs, 2018)
OBJECTIVE: Young adult substance use is linked with the risk of substance use disorders (SUDs) later in adulthood. Marriage may be part of this pathway because of both selection effects (early substance use reducing marriage) and socialization effects (marriage reducing later substance use and disorder). We examine whether marital status mediates the association between young adult substance use and subsequent SUDs, using causal mediation methods to strengthen inferences. METHOD: Using panel data from high school seniors in 1990–1998, we examined whether the effects of two exposures (level of alcohol/marijuana use at age 19/20) on the outcomes (alcohol use disorder [AUD]/marijuana use disorder [MUD], nondisordered use, or abstinence at age 35) were mediated by marital status at age 29/30. Propensity score weights adjusted for potential confounding regarding both the exposures and the mediator. RESULTS: Moderate and heavy alcohol/marijuana use at age 19/20 were associated with higher odds of AUD/MUD and lower odds of abstinence, each relative to nondisordered use, at age 35. The association between heavy alcohol use at age 19/20 and subsequent AUD was partially mediated by being unmarried at age 29/30; the associations between moderate and heavy marijuana use at age 19/20 and subsequent marijuana abstinence were partially mediated by being unmarried at age 29/30. CONCLUSIONS: Both selection and socialization effects related to marriage explain the perpetuation of substance use behaviors across adulthood. Selection effects on marriage seem to occur at different thresholds for young adult alcohol and marijuana use.